PTH-121 Referral pathway and age influence the likelihood of biopsy to exclude eosinophilic oesophagitis in dysphagia. (8th June 2018) - Hadjinicolaou, Andreas; Beg, Sabina; Tun, Gloria; Warburton, Louise; Sansone, Stefano; Riley, Stuart; Ragunath, Krish; Modolell, Ines
Abstract : Introduction: Dysphagia is a common cause for 2 week wait (2 WW) referral for endoscopy, where the primary goal is to exclude malignancy. Non-malignant pathology such as Eosinophilic Oesophagitis (EO) can present with similar symptoms. As EO may have little in the way of endoscopic features, it is recommended that biopsies be taken to exclude this condition where no endoscopic cause is found. It is unknown whether this strategy is appropriate in the rapid access population. Methods: We performed a database review of all OGDs performed to investigate dysphagia, during the 12 month period of 1 st July 2016 – 30th June 2017, within three large teaching hospitals serving a population of 3.2 million. Demographic information, endoscopic diagnosis and histology results were evaluated. Biopsy practice and outcomes were compared according to referral pathway and patient age. Results: During this period of time 3052 patients underwent an OGD for dysphagia, of which 2387 (64%) were investigated on the 2 WW pathway and 665 (17.9%) as routine referrals. In cases where no cause for dysphagia was identified on endoscopy, biopsy to exclude EO was more likely in patients under routine referral compared to those on the 2 WW pathway (table 1). EO was over three times more commonly diagnosed in the routine referral cohort. Patient age also influenced the likelihood of taking biopsies, with a negative correlation between biopsy acquisition and patient age (table 2). Overall, there were 68 histologically confirmed diagnoses of EO with mean age of 42 years and M:F ratio of 2:1. Conclusions: Our data suggest that despite no significant differences in demographics, those referred via the 2 WW were less likely to be investigated for EO than those referred routinely. Patient age appears to influence the investigation of EO, despite proven cases in older patients. These disparities in practice may result in under diagnosis of EO in older patients or patients referred through the 2WW pathway.